Palliative Care, a discipline that humanizes medical practice at the end of life: Some contributions from Psychology - Cabrera, María Emilia (2021)
The following work has the aim to develop and present the vicissitudes that patients diagnosed with a life-threatening disease, which makes them face the possibility of death, experience. Special mention and emphasis will be made on the contributions that can made from Palliative Care and, especially from our discipline, Psychology. Firstly, we start by raising some questions and concerns that we have as mental health professionals, which will give room to debate and theoretical articulation. Secondly, we provide contributions that, from Psychology, help to humanize medical practice at the end of life: they bet on subjectivity, on listening to the patient and his/her family and on enabling them to have a voice in the process of living and dying. Thirdly, we present and describe in greater detail what is theorized from Lev Tolstoy's novel ‘The Death of Ivan Ilyich’, taking different passages. In his book, this author, by means of a fictionalized, descriptive and figurative narrative, represents the difficulties that a person diagnosed with a disease without any curative treatment has to go through.